(untitled) (Bangladesh Journal of Child Health, 2014)
Background: The aim of the study was to unveil the prevalence of different types of Congenital Heart Disease (CHD) through echocardiogram and to perceive the utility of Echocardiogram in diagnosis of CHD in Infant of Diabetic Mother (IDM). Methodology: This explorative study was carried out at Combined Military Hospital (CMH) Dhaka, Bangladesh over a period of one year from July 2004 to June 2005. The study was done on 56 neonates of gestational diabetic mother irrespective of their gestational age and birth weight who were delivered at CMH. All the patients were evaluated by echocardiography by an expert pediatric cardiologist of the same institute within 7 days of delivery. Results: Out of 56 IDM 5.2% was normal. The most common Echo-cardiographic finding was patent Foramen Ovale (60.71%). Other different Echocardiographic findings were patent Ductusarteriosusin 31 (55.3%) cases, Hypertrophic Cardiomyopathy in 12 (21.42%) cases and ASD in 6 (10.71%) cases. Some other uncommon findings include Ventricular Septal Defect (VSD), Tricuspid Regurgitation(TR) and Right ventricular hypertrophy(RVH). Conclusion: These findings of CHD of Infant of Diabetic Mother (IDM) could demonstrate that Echocardiogram might be used as an effective tool to diagnose CHD for the IDM. DOI: http://dx.doi.org/10.3329/bjch.v38i2.21140 Bangladesh J Child Health 2014; VOL 38 (2) : 74-78